Tiempo y modo en las subordinadas sustantivas - González Rodríguez, Raquel (Dicenda. Estudios de lengua y literatura españolas, 2003)
This paper aims to describe the tense-mood relation established in embedded clauses. This research focuses on the possible temporal independence of the subjunctive mood. It shows that the matrix verb is capable of determining the dependence or temporal independence of the subjunctive in the embedded clause. A formal analysis situated within the framework of the Minimalist Program is proposed for these verb forms. Finally, the relation between this grammatical aspect and negative polarity licensing is shown and explained.